2015
DOI: 10.1590/0100-2945-120/14
|View full text |Cite
|
Sign up to set email alerts
|

Amido E Hipoclorito De Sódio No Enraizamento in Vitro Do Abacaxizeiro ‘Gold’ E Seus Efeitos Na Aclimatização

Abstract: RESUMO-Este trabalho teve como objetivo avaliar a substituição total ou parcial do ágar por amidos de milho e mandioca e da esterilização física em autoclave pela esterilização química com hipoclorito de sódio (NaClO) no desenvolvimento de mudas de abacaxizeiro 'Gold' (Ananas comosus). Como agentes geleificantes, foram utilizados: M1: ágar (6,0 g L -1 ); M2: amido de milho (60,0 g L -1 ); M3: ágar (3,0 g L -1 ) + amido de milho (30,0 g L -1 ), e M4: ágar (3,0 g L -1 ) + amido de mandioca (30,0 g L -1 ). As est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…In experiments with other fruit trees, such as the pineapple cultivar 'Vitória', the sprout survival in culture media with different structuring agents, such as pure maize (Zea mays) starch oragar with partial or total addition of starch, did not differ from that in agar media. Thus, plants cultivated in environments with corn starch showed a similar development to those cultivated in agar (OLIVEIRA et al 2015a).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In experiments with other fruit trees, such as the pineapple cultivar 'Vitória', the sprout survival in culture media with different structuring agents, such as pure maize (Zea mays) starch oragar with partial or total addition of starch, did not differ from that in agar media. Thus, plants cultivated in environments with corn starch showed a similar development to those cultivated in agar (OLIVEIRA et al 2015a).…”
Section: Resultsmentioning
confidence: 80%
“…In order to reduce the costs of micropropagation, research to replace reagents such as agar with alternative solidifying materials for culture media that also allow for adequate development of the explants has been conducted. For example, GOLLE et al (2010) experimented with corn starch, vermiculite, filter paper, and hydrophilic cotton for micropropagation of the loblolly pine (Pinus taeda), CURTI & REINIGER (2014) tested vermiculite, Plantmax ® , and fine sand in yellow poinciana (Peltophorum dubium), OLIVEIRA et al (2015aOLIVEIRA et al ( , 2015b tested corn starch and cassava starch in pineapple (Ananas comosus), andRODRIGUES et al (2016) andNADAL et al (2018) assessed the use of coconut fiber, carbonized rice husk, and in natura rice husk for propagation of golden rain orchid (Oncidium baueri).…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic index (PI) is used to interpret responses of plants subjected to stress conditions: a PI lower than 1.0 represents a critical point (OLIVEIRA et al, 2015). This variable considers structural and functional events that occur in the PSI and PSII (GONÇALVES et al, 2005).…”
Section: Vegetative Stagementioning
confidence: 99%
“…Soares et al (2014) who studied in vitro cultivation of Dendrobium nobile Lindl., reported that replacing 50% of agar for maize starch provided higher plant growth in culture media sterilized by autoclaving. Studies conducted with pure maize starch or cassava starch combined with agar in culture media sterilized by autoclaving showed that they were effective in culture media solidifying agents in the in vitro rooting of 'Gold' pineapples (Oliveira et al, 2015). Vieira (2018) analyzed the hydrogel to replace agar in vitro showing potential to be used in the in vitro cultivation of A. thaliana.…”
Section: Gelling Agents Used In Thermal Sterilizationmentioning
confidence: 99%